Descriptive Analysis of 213 Positive Blood Aspiration Cases When Injecting Facial Soft Tissue Fillers. (6th June 2020) - Tseng, Fang Wen; Bommareddy, Kanthi; Frank, Konstantin; DeLorenzi, Claudio; Green, Jeremy B; Sadick, Neil; Fitzgerald, Rebecca; Onishi, Emy C; Swift, Arthur; Cotofana, Sebastian
Abstract: Background: Pre-injection aspiration procedures could increase safety during soft tissue filler injections. However, various influencing factors have been detected in vitro that could result in false negative aspiration results. Objective: A case series was retrospectively investigated to identify factors contributing to positive blood aspiration procedures in vivo. Methods: This study evaluated 213 clinical cases positive for blood aspiration documented in an Asian population: 208 females (43.8 ± 7.2 years old) and 5 males (46.8 ± 7.8 years old) during soft tissue filler injections. Injection location, layer (depth) of injection, product injected, size of utilized needle (gauge), length of needle (inch), priming of needle (yes/no), injection angle (degree), and time until blood was visible in the needle hub (seconds) were evaluated. Results: The most frequent location where a positive aspiration was observed was the pyriform fossa (n = 56; 26.3%), the most frequent plane was the supra-periosteal plane (n = 195; 91.5%), and the most frequent needle utilized was a 27G needle (n = 125; 58.7%). Statistically significantly more positive cases were identified when the needle was primed compared with an unprimed needle ( P  < 0.001, which was independent of the product). The estimated incidence rate was 0.04% to 0.9% for having positive aspiration procedures per total performed injection procedures. Conclusions: Pre-injection aspiration could be a valuable tool to prevent accidental intravascular injection of soft tissue filler. The results of the present investigation show that aspiration can be performed with an acceptable aspiration time, that is, less than 2 seconds, if a suitable product/needle combination is chosen. Level of Evidence: 4: